Assessment of genetic literacy for biology pre-service teacher - Ali Mustofa; Heru Kuswantoro; Siti Zubaidah; Hidayati Maghfiroh (Bioedukasi: Jurnal Pendidikan Biologi, 2024)
Genetic literacy is the capacity to obtain, process, understand, and use genetic information. Genetic literacy is a supportive thing in understanding science as a theory, process, and application. Genetic literacy that is empowered in learning can develop cognitive and affective aspects in pre-service teachers. This study aims to measure genetic literacy skills as a preliminary study for further research on the genetic literacy skills of students in genetics courses. This research design refers to descriptive research. The research subjects in this study were Universitas PGRI Ronggolawe biology education students who took genetics courses for the 2019/2020 academic year. The genetic literacy skill instrument was validated through product-moment correlation analysis. There are 15 genetic literacy questions with right and wrong answer choice and multiple choice questions. Scores will be interpreted into percentages and grouped into high, satisfactory, under-satisfactory, and unsatisfactory categories. The results showed that genetic literacy tests on 25 college students showed that the highest score was 93 and the lowest score was 73. The average genetic literacy score of students was 82.7. Based on genetic literacy test questions, it shows that the concept of student understanding is in the excellent category. This phenomenon is influenced by various factors, including the learning design and teaching materials used. The concept of good student knowledge showed high results in genetic literacy skills in this study.